Insecticidal effect of three insecticides applied on different surfaces for the control of three stored-product beetle species. (March 2023) - Lampiri, Evagelia; Agrafioti, Paraskevi; Athanassiou, Christos G.
Abstract: We evaluated the efficacy of alpha-cypermethrin, deltamethrin and spinosad on concrete, ceramic, plastic and metallic surfaces against found major stored-product beetle species, the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), the rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae), and the sawtoothed grain beetle, Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae). For alpha-cypermethrin, deltamethrin and spinosad the dose rates applied to surfaces were 0.01, 0.05, and 0.1 mg (Al)/cm −2, respectively. All three insecticides were applied at the label dose, while the bioassays were carried out against the adult stage of the three target species. Mortality was assessed after 3, 7 and 14 days of exposure. The results of the present study revealed that the active ingredient with the highest efficacy for all species was spinosad, while the most tolerant species for all the active ingredients evaluated was T. confusum. Surface type was significant for all species, except for T. confusum . Concrete reduced the efficacy of deltamethrin, while ceramic reduced the efficacy of spinosad. Regarding the overall data, spinosad and deltamethrin can effectively control the species tested here, but there are certain factors that affect their efficacy, such as the exposure interval and the type of the surface. Highlights: Concrete and ceramic surface contribute to a reduced effectiveness of deltamethrin and spinosad, respectively. The most effective insecticidal formulation was spinosad, followed by deltamethrin and alpha-cypermethrin. T. confusum was the least susceptible insect species for all insecticides examined.